Effects of the time of drought occurrence within the growing season on growth and survival of Pinus ponderosa seedlings - Fernandez, María Elena (2014)
Although there is certainty about the increasing frequency of extreme climatic events, the consequences of changing patterns of drought events within the growing season on the growth and survival of different species are much less certain. In particular, little knowledge is available on the differential effect on tree seedlings of a drought event at different times within the growing season. The objective of this study was to quantify the effect of a drought event imposed at different times over the growing season on the growth, survival and some related morphological and physiological variables of Pinus ponderosa seedlings from two seed sources. Four treatments were applied: control conditions; spring drought; summer drought and spring plus summer drought (SpSuD). A drought event in spring reduced stem growth and biomass accumulation in ponderosa pine seedlings during the occurrence of the drought and afterwards, even when plant water status had recovered. The lack of growth recovery could not be associated with loss of stem hydraulic conductivity or reduction in stomatal conductance after drought. However, the spring drought did not differentially affect plant survival, as was the case with prolonged drought in the SpSuD treatment. The summer drought event had a significant but much smaller impact on plant growth. Our results suggest different consequences of a drought event in spring or in summer in ponderosa pine seedlings. This knowledge may be relevant to understand and predict tree seedlings responses to changing patterns of drought events within the growing season in the framework of climatic change.